Ethnic differences in genetic polymorphism associated with irritable bowel syndrome - Xiao, Qi-Yun (World J Gastroenterol, 2020)
Genetic polymorphism is associated with irritable bowel syndrome (IBS) in terms of susceptibility and clinical manifestations. Previous studies have shown that genetic polymorphism might play a key role in the onset and progression of IBS by modulating components of its pathogenesis such as the gut-brain axis, gastrointestinal motility, inflammatory activity, and immune status. Although underlying pathophysiological mechanisms have not been fully clarified, the potential ethnic differences that are present in worldwide genetic studies of IBS deserve attention. This review surveyed numerous studies focusing on IBS-associated single nucleotide polymorphisms, and investigated the ethnic disparities revealed by them. The results demonstrate the need for more attention on ethnic factors in IBS-related genetic studies. Taking ethnic backgrounds into accounts and placing emphasis on disparities potentially ascribed to ethnicity could help lay a solid and generalized foundation for transcultural, multi-ethnic, or secondary analyses in IBS, for example, a meta-analysis. Broader genetic studies considering ethnic factors are greatly needed to obtain a better understanding of the pathophysiological mechanisms of IBS and to improve the prevention, intervention, and treatment of this disease.